Inside story e-commerce in business - Leigh, Richard (Bendigo, Victoria : Video Education Australasia, 2003)
Summary: This accessible current-affairs format leads viewers to where information technology meets everyday life. In three self-contained stories, this program provide three fascinating case studies: Ford, with their online marketing ; Coronet, with their online ordering system, and ; Mp3.com.au, with their online dlivery of music.
Executive producer, Mark McAuliffe ; editor, Damien Bear
Host: Eleanor Handley, Jim Pidgeon
Keywords: Electronic commerce